HUBUNGAN PERDARAHAN GASTROINTESTINAL DENGAN LUARAN PASIEN STROKE ISKEMIK AKUT - Rico Defryantho; Lisda Amalia; Ahmad Rizal; Suryani Gunadharma; Siti Aminah; Nushrotul Lailiyya (PERDOSNI, 2019)
ASSOCIATION BETWEEN GASTROINTESTINAL BLEEDING WITH CLINICAL OUTCOME ACUTE ISCHEMIC STROKE PATIENTABSTRACTIntroduction: Gastrointestinal bleeding associated by the delay in the administration of antiplatelet and anticoagulant, thus affected the clinical outcome and patient treatment.Aims: To find the association between gastrointestinal bleeding and clinical outcome in acute ischemic stroke patient.Methods: This study was a prospective observational, conducted at Hasan Sadikin Hospital Bandung in November 2017 to February 2018. Acute ischemic stroke patients that fulfill the inclusion and exclusion criteria were observed while being treated in the ward and the survival rate and length of stay were studied. This study used univariate, bivariate, multivariate, and stratification analysis.Results: In the study period, 100 acute ischemic stroke patients were found and 24 patients had gastrointestinal bleeding. A history of previous peptic ulcer/gastrointestinal bleeding was found in patient with gastrointestinal bleeding (20.8%). Median NIHSS score was higher (16 vs 7) and GCS score was lower (12 vs 15) in patients with bleeding. Multivariate analysis showed that gastrointestinal bleeding were significantly associated with survival and length of stay. The analysis of stratification showed subjects with infections who later experienced gastrointestinal bleeding had a lower risk of death and length of stay than subjects without infection who experienced gastrointestinal bleeding (1.7 vs 22.5 times and 1.5 vs 2 times).Discussion: Ischemic stroke with gastrointestinal bleeding had higher mortality and length of stay than without gastrointestinal bleeding in acute ischemic stroke patient.Keyword: Acute ischemic stroke, gastrointestinal bleeding, length of stay, mortalityABSTRAKPendahuluan: Perdarahan gastrointestinal berhubungan dengan penundaan terapi antiplatelet atau antikoagulan, sehingga berpengaruh terhadap luaran dan tata laksana pasien.Tujuan: Mengetahui hubungan perdarahan gastrointestinal dengan luaran pasien stroke iskemik akut.Metode: Penelitian prospektif observasional terhadap pasien stroke iskemik akut di RSUP Dr. Hasan Sadikin, Bandung pada bulan November 2017 hingga Februari 2018. Pasien stroke iskemik akut yang memenuhi kriteria inklusi dan eksklusi diobservasi selama perawatan untuk mengetahui survival dan lama perawatan di rumah sakit. Analisis statistik yang digunakan adalah univariat, bivariat, multivariat, dan stratifikasi.Hasil: Selama periode penelitian didapatkan 100 subjek stroke iskemik akut dengan 24 subjek mengalami perdarahan gastrointestinal. Riwayat ulkus peptikum/perdarahan gastrointestinal sebelumnya sebanyak 20,8% pada perdarahan gastrointestinal. Median skor NIHSS lebih tinggi (16 vs 7) dan skor GCS lebih rendah (12 vs 15) pada perdarahan. Analisis multivariat didapatkan perdarahan gastrointestinal memiliki hubungan signifikan dengan survival dan lama perawatan. Berdasarkan analisis stratifikasi subjek dengan infeksi yang kemudian mengalami perdarahan gastrointestinal memiliki risiko mortalitas dan lama perawatan lebih rendah dibandingkan subjek tanpa infeksi kemudian mengalami perdarahan gastrointestinal (1,7 vs 22,5 kali dan 1,5 vs 2 kali).Diskusi: Stroke iskemik akut yang mengalami perdarahan gastrointestinal memiliki risiko mortalitas dan lama perawatan lebih tinggi dibandingkan tanpa perdarahan gastrointestinal.Kata kunci: Lama perawatan, mortalitas, perdarahan gastrointestinal, stroke iskemik akut